Crowding does not affect monarch butterflies' resistance to a protozoan parasite. Issue 4 (6th April 2022) - Alaidrous, Wajd; Villa, Scott M.; de Roode, Jacobus C.; Majewska, Ania A.
Abstract: Host density is an important factor when it comes to parasite transmission and host resistance. Increased host density can increase contact rate between individuals and thus parasite transmission. Host density can also cause physiological changes in the host, which can affect host resistance. Yet, the direction in which host density affects host resistance remains unresolved. It is also unclear whether food limitation plays a role in this effect. We investigated the effect of larval density in monarch butterflies, Danaus plexippus, on the resistance to their natural protozoan parasite Ophryocystis elektroscirrha under both unlimited and limited food conditions. We exposed monarchs to various density treatments as larvae to mimic high densities observed in sedentary populations. Data on infection and parasite spore load were collected as well as development time, survival, wing size, and melanization. Disease susceptibility under either food condition or across density treatments was similar. However, we found high larval density impacted development time, adult survival, and wing morphology when food was limited. This study aids our understanding of the dynamics of environmental parasite transmission in monarch populations, which can help explain the increased prevalence of parasites in sedentary monarch populations compared to migratory populations. Abstract : Crowding of hosts can have consequences on susceptibility and resistance to pathogens. In this study, we used the monarch butterfly and its protozoan to examine whether host density has an impact on infection probability and infection load when food is unlimited or limited. We found no effect on infection susceptibility or resistance in either food scenarios, yet strong effects on adult morphology with food limitation.